Ultrafast X-ray absorption study of longitudinal–transverse phonon coupling in electrolyte aqueous solution. Issue 40 (9th October 2017) - Jiao, Yishuo; Adams, Bernhard W.; Dohn, Asmus Ougaard; Møller, Klaus B.; Jónsson, Hannes; Rose-Petruck, Christoph
Abstract : Ultrafast X-ray absorption spectroscopy is applied to study the conversion of longitudinal to transverse phonons in aqueous solution. Abstract : Ultrafast X-ray absorption spectroscopy is applied to study the conversion of longitudinal to transverse phonons in aqueous solution. Permanganate solutes serve as X-ray probe molecules that permit the measurement of the conversion of 13.5 GHz, longitudinal phonons to 27 GHz, transverse phonons that propagate with high-frequency sound speed. The experimental results, combined with QM/MM MD simulations, show that the hydrogen bond network around the charged solutes has a glass-like stiffness that persists for at least tens of picoseconds.